Liposarcoma in the Inguinal Canal: Challenges in Preoperative Diagnosis and Importance of Routine Pathological Examination of “Hernia Sacs” - Christopher A. Febres-Aldana; Jin Min; Marc Rafols; Irvin Willis; John Alexis (Case Reports in Pathology)
Liposarcoma is the most common histologic subtype of soft tissue sarcoma in the retroperitoneum. The distinction of primary cord liposarcomas, which arise in and are confined to the inguinal canal, from inguinoscrotal extension of a retroperitoneal tumor is mandatory. Both can be found incidentally in inguinal hernia sac specimens. Preoperative diagnosis is essential for adequate surgery with clear margins. We present a clinicopathological correlation of two men with slowly growing right para-testicular masses diagnosed as inguinal hernias. Pathological examination revealed well-differentiated lipoma-like liposarcoma and well-differentiated liposarcoma mixed type (lipoma-like and sclerosing types), respectively. The first tumor was considered a primary cord liposarcoma with no recurrence on follow-up. The second tumor showed an unusual growth pattern of discontinuous nodules that gave the false impression of complete resection. This growth pattern may explain why inguinal liposarcomas have a high recurrence rate despite apparently negative surgical margins. A follow-up CT scan exposed a fatty tumor in the retroperitoneum of the second patient. Careful interpretation of imaging studies in patients with fatty inguinal masses is mandatory to rule out a retroperitoneal or intraperitoneal component. Although the two cases herein discussed represent less than 0.1% of the total inguinal hernia sacs examined over the past five years in our pathology department, we recommend routine examination of all “mass-containing” hernia sacs as missing the diagnosis of liposarcoma can lead to substantial morbidity and mortality.